2019
DOI: 10.1136/jnnp-2018-319714
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II alleleDRB1*16:02is associated with anti-NMDAR encephalitis

Abstract: Background and objectiveAetiology and pathogenesis of anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis, the most common autoimmune encephalitis, is largely unknown. Since an association of the disease with the human leucocyte antigen (HLA) has not been shown so far, we here investigated whether anti-NMDAR encephalitis is associated with the HLA locus.MethodsHLA loci of 61 patients with anti-NMDAR encephalitis and 571 healthy controls from the Chinese Han population were genotyped and analysed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 40 publications
2
50
1
Order By: Relevance
“…No strong HLA association has been reported with anti-NMDAR encephalitis thus far [84,95]. DRB1*16:02 was found to be more frequent in patients than in controls, but it accounted for less than 15% of the alleles of a series of 61 patients (vs. less than 5% in control group; p < 0.05, OR = 3.41, 95% CI [1.81-6.17]) [96]. Moreover, carrier frequencies between paraneoplastic (mostly ovarian teratomas) and non-paraneoplastic cases were similar.…”
Section: Encephalitis With Anti-n-methyl-d-aspartate Receptor Autoantmentioning
confidence: 85%
See 1 more Smart Citation
“…No strong HLA association has been reported with anti-NMDAR encephalitis thus far [84,95]. DRB1*16:02 was found to be more frequent in patients than in controls, but it accounted for less than 15% of the alleles of a series of 61 patients (vs. less than 5% in control group; p < 0.05, OR = 3.41, 95% CI [1.81-6.17]) [96]. Moreover, carrier frequencies between paraneoplastic (mostly ovarian teratomas) and non-paraneoplastic cases were similar.…”
Section: Encephalitis With Anti-n-methyl-d-aspartate Receptor Autoantmentioning
confidence: 85%
“…Moreover, carrier frequencies between paraneoplastic (mostly ovarian teratomas) and non-paraneoplastic cases were similar. The only observed clinical difference was a possible worse response to treatment in DRB1*16:02 carriers [96]. Finally, in a genome-wide association study, a weak association with B*07:02 was described in adult patients with anti-NMDAR encephalitis (21% of the alleles of a sample of n = 49; p < 0.05, OR = 2.32, 95% CI [1.34-4.00]) [95].…”
Section: Encephalitis With Anti-n-methyl-d-aspartate Receptor Autoantmentioning
confidence: 96%
“…The phenomenons are not rare that one autoimmune disease increases the chance of an additional autoimmune disease, and that autoimmune disease patient has multiple positive antibodies. Recent studies have shown that anti-NMDAR encephalitis was associated with the HLA alleles (23,24). Perhaps, genetic predisposition is the important reason for the increased prevalence of systemic autoantibodies in patients with anti-NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…In their JNNP paper, Shu et al investigated whether anti-NMDAR encephalitis was associated with any HLA alleles, utilising samples from 61 patients with anti-NMDAR encephalitis and 571 healthy controls from the Chinese Han population 4. In this study, six HLA loci ( HLA-A , HLA - B , HLA - C , HLA - DRB1 , HLA -DQA1 and HLA -DQB1 ) were typed using a PCR sequence-based typing method, while the German study mentioned above imputed HLA alleles from single nucleotide polymorphisms (SNPs) genotyped on a genome-wide SNP chip array 2.…”
Section: Hla-drb1*16:02 Is a Disease Susceptibility Allele For Anti-nmentioning
confidence: 99%